Coloniality of International Climate Litigation and Climate (In-)Justice: Exploring Challenges and Perspectives from the Global South - Mehak Ali; Muhammad Manzoor Elahi; Muhammad Azeem Farooqi (Social Science Review Archives, 2025)
This research delves into the intersection of coloniality and climate (in-)justice vis-a-vis litigation efforts by the Global South. The objective is to mainly explore how historical and ongoing patterns of neo-colonialism shape legal framework of climate governance and often cause marginalization and climate injustice to poor nations of the Global South. A qualitative exploratory-cum-analytical approach is applied under critical lens of post-colonial framework to analyse the litigation case studies, historical inequalities and legal frameworks. The findings uncovers the significant barriers in seeking climate justice i.e., structural biases, north-dominated litigations, inaccessibility to resources, political marginalization, locus standi and causation, and advisory opinion for small island states. The study concludes with a way forward that decoloniality of climate litigation is essential to seek equitable and inclusive global climate justice.